Brennan, Patricia interview - (:unkn) unknown (My University, 2010)
Patricia F. Brennan is the Lillian S. Moehlman-Bascom Professor of Nursing and Industrial Engineering. She is also the theme leader of the Living Environments Laboratory at the Wisconsin Institutes for Discovery. This interview documents her involvement with the early conceptualization and development of the Wisconsin Institutes for Discovery.